2010
DOI: 10.1097/iop.0b013e3181c3252c
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Flap Anastomosis in External Dacryocystorhinostomy

Abstract: The inferior flap design simplifies the surgical procedure and produces success rates comparable with those found in conventional DCR. Further studies with larger numbers of patients are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…8 Therefore, suturing the posterior flaps may be relatively difficult and limiting stage for surgeons who are not well-experienced, due to limited area especially in the presence of hemorrhage. 11,12 Thus, several alternative techniques in flap design have been currently suggested with similar degrees of success rates. [8][9][10][11][12] Baldeschi et al 8 compared 3 different patterns of mucosal flap design (anterior and posterior, extended anterior with posterior and only anterior) in external DCR.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…8 Therefore, suturing the posterior flaps may be relatively difficult and limiting stage for surgeons who are not well-experienced, due to limited area especially in the presence of hemorrhage. 11,12 Thus, several alternative techniques in flap design have been currently suggested with similar degrees of success rates. [8][9][10][11][12] Baldeschi et al 8 compared 3 different patterns of mucosal flap design (anterior and posterior, extended anterior with posterior and only anterior) in external DCR.…”
Section: Discussionmentioning
confidence: 98%
“…11,12 Thus, several alternative techniques in flap design have been currently suggested with similar degrees of success rates. [8][9][10][11][12] Baldeschi et al 8 compared 3 different patterns of mucosal flap design (anterior and posterior, extended anterior with posterior and only anterior) in external DCR. They found that the success rates among 3 groups differing in flap design were similar.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Arka flep oluşturulması ve sütürasyonu aşaması derin ve dar bir alanda çalışmayı gerektirdiğinden, bu durum cerrahi süresinin uzamasına; kanama ve flep zedelenmesi gibi komplikasyonlara neden olabilmektedir. 16,17 Bu aşamayı kısaltmak ve kolaylaştırmak için bir çok teknik değişiklik yapılagel-miştir. Literatürde arka flebin eksizyonu ve sütüre edilmemesi, değişik şekilli mukozal fleplerin oluştu-rulmasına ait raporlar bulunmaktadır.…”
Section: Discussionunclassified